Analysis and prediction of the burden of lung cancer attributable to diet low in fruits in China and the global from 1990 to 2021 - Caifa Ji; Youjian Yao; Mei Gui (PLoS ONE, 2026)
Objectives To analyze the trend of the disease burden of lung cancer attributable to diet low in fruits among the Chinese and the global populations from 1990 to 2021, describe the disease burden situation in 2021, and predict the development trend of the disease burden attributable to diet low in fruits over the next 25 years, so as to provide scientific suggestions for the prevention and control of lung cancer. Methods The paper utilized data from the Global Burden of Disease Study 2021 (GBD 2021). The joinpoint regression model was employed to calculate the annual percentage change (APC) and the average annual percentage change (AAPC) to assess the changing trend of the burden of lung cancer attributable to diet low in fruits. The disease burden of lung cancer attributable to diet low in fruits was predicted for the next 25 years using a Bayesian age-period-cohort (BAPC) model. Results From 1990 to 2021, the number of mortality and disability-adjusted life years (DALY) of lung cancer attributable to diet low in fruits in China and the global increased significantly, while the age-standardized rates decreased significantly. In China, the estimated annual percentage change (EAPC) in the total population and different gender categories ranged from −4.0 to −2.8. The mortality number of lung cancer attributable to diet low in fruits in China increased with age, reaching a peak at 70−74 years. Similarly, the age-standardized DALY rate paralleled mortality rate trends across genders and age groups. The AAPC in age-standardized mortality and DALY rates were −2.69 and −3.15, respectively. According to the BAPC model prediction results that by 2046, the age-standardized mortality and DALY rates of lung cancer attributable to diet low in fruits in China and the global will decrease by 31.58%, 24.68%, 29.28%, and 24.34%, respectively. Conclusions From 1990 to 2021, the mortality and DALY rates of lung cancer attributable to diet low in fruits in China and the global both decreased. The disease burden of lung cancer attributable to diet low in fruits in male has always been higher than that in female, and the mortality and DALY rates were the highest among the elderly. It is expected that by 2046, the mortality and DALY rates of lung cancer attributable to diet low in fruits will further decrease.